Otitis media: recent advances in otitis media vaccine development and model systems - Zahid, Ayesha; Wilson, Jennifer C.; Grice, I. Darren; Peak, Ian R. (Frontiers in Microbiology, 2024)
Otitis media is an inflammatory disorder of the middle ear caused by airways-associated bacterial or viral infections. It is one of the most common childhood infections as globally more than 80% of children are diagnosed with acute otitis media by 3 years of age and it is a common reason for doctor’s visits, antibiotics prescriptions, and surgery among children. Otitis media is a multifactorial disease with various genetic, immunologic, infectious, and environmental factors. Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis are the most common culprits responsible for acute otitis media. Despite the massive global disease burden, the pathogenesis of otitis media is still unclear and requires extensive future research. Antibiotics are the preferred treatment to cure middle ear infections, however, the antimicrobial resistance rate of common middle ear pathogens has increased considerably over the years. At present, pneumococcal and influenza vaccines are administered as a preventive measure against otitis media, nevertheless, these vaccines are only beneficial in preventing carriage and/or disease caused by vaccine serotypes. Otitis media caused by non-vaccine serotype pneumococci, non-typeable H. influenza, and M. catarrhalis remain an important healthcare burden. The development of multi-species vaccines is an arduous process but is required to reduce the global burden of this disease. Many novel vaccines against S. pneumoniae, non-typeable H. influenza, and M. catarrhalis are in preclinical trials. It is anticipated that these vaccines will lower the disease burden and provide better protection against otitis media. To study disease pathology the rat, mouse, and chinchilla are commonly used to induce experimental acute otitis media to test new therapeutics, including antibiotics and vaccines. Each of these models has its advantages and disadvantages, yet there is still a need to develop an improved animal model providing a better correlated mechanistic understanding of human ME infections, thereby underpinning the development of more effective otitis media therapeutics. This review provides an updated summary of current vaccines against otitis media, various animal models of otitis media, their limitations, and some future insights in this field providing a springboard in the development of new animal models and novel vaccines for otitis media.